2015
DOI: 10.1111/jam.12731
|View full text |Cite|
|
Sign up to set email alerts
|

Control of eight predominant Eimeria spp. involved in economic coccidiosis of broiler chicken by a chemically characterized essential oil

Abstract: This study provides information about the possibility of using this blend of essential oil as a coccidiostat for the protection of broiler chickens against the prevalent eight Eimeria spp. of coccidiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Similar response was reported by Al‐Fataftah and Abdelqader (), in which birds received 100 ppm eucalyptus extract in drinking water, and had higher BWG and lower FCR compared with control birds. Barbour et al () showed that the growth performance of coccidia‐challenged broilers was improved ( p < 0.05) when a commercial blend containing eucalyptus and peppermint oils was added to the drinking water. The major components of EOB are carvacrol (28.20%), menthol (16.62%), thymol (9.40%), ρ‐cymene (9.25%), 1,8‐cineol (5.70%), menthone (4.84%), γ‐terpinene (4.49%) and α‐pinene (3.10%) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar response was reported by Al‐Fataftah and Abdelqader (), in which birds received 100 ppm eucalyptus extract in drinking water, and had higher BWG and lower FCR compared with control birds. Barbour et al () showed that the growth performance of coccidia‐challenged broilers was improved ( p < 0.05) when a commercial blend containing eucalyptus and peppermint oils was added to the drinking water. The major components of EOB are carvacrol (28.20%), menthol (16.62%), thymol (9.40%), ρ‐cymene (9.25%), 1,8‐cineol (5.70%), menthone (4.84%), γ‐terpinene (4.49%) and α‐pinene (3.10%) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing interest in using essential oils against coccidiosis infection. The supplementation of essential oils led to a significant reduction of coccidian oocyst excretion and an alleviation of intestinal lesions in chicks ( Alp et al., 2012 , Bozkurt et al., 2014 , Barbour et al., 2015 ). However, the underlying mechanisms still need to be elucidated.…”
Section: Essential Oils For Poultrymentioning
confidence: 99%
“…Protective effect of EO on Eimeria-specific lesions was reported elsewhere [27]. However, no clear effect of SAL or EEO on gut lesion scores was noted.…”
Section: Discussionmentioning
confidence: 60%